On the Effect of Pouring Temperature on Spheroidal Graphite Cast Iron Solidification - Schulz-Eglin, B; Cruchaga-Ssa., M (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
This work is focused on the effect of pouring temperature on the thermal-microstructural response of an eutectic spheroidal graphite cast iron (SGCI). To this end, experiments as well as numerical simulations were carried out. Solidification tests in a wedge-like part were cast at two different pouring temperatures. Five specific locations exhibiting distinct cooling rates along the sample were chosen for temperature measurements and metallographic analysis to obtain the number and size of graphite nodules at the end of the process. The numerical simulations were performed using a multinodular-based model. Reasonably good numerical-experimental agreements were obtained for both the cooling curves and the graphite nodule counts. © 2015 by the authors; licensee MDPI, Basel, Switzerland.